Nursing - history and development of the profession - Wierzbicka, Iwona Bożena (Journal of Education, Health and Sport, 2019)
The article presents selected key issues that have conditioned the creation of the nursing profession, it’s history, both in the world and in Poland. The influence of the events that changed nursing in Poland from charitable- social activites to independent, self-contained profession was described in the article. The origins of nursing, which reached even to ancient times underwent continuous transformation in the subsequent centuries. All these changes took place thanks to the creators, reformers and organizations. The creation of the International Council of Nurses has contributed to increase the prestige of the profession. There has been a process associated with the development of nursing education and nursing schools, the first to the twenty-first century, where university education universally valid. The legal basis for the profession of nursing and midwifery has been regulated by the Law of 5 July 1996. Based on our review of the literature it found that nursing in Poland changed over the years, but at the present time to struggle with problems, inter alia associated with a deficit of nurses and graduates emigrating abroad in search of work conditioned higher wages than in their native country.